3D model of biomechanical system elements rotation around arbitrary axis - Zagrevskiy, V. I.; Zagrevskiy, O. I. (Theory and Practice of Physical Culture, 2017)
Background: Human motor action may be interpreted as a 3D combination of progressive and rotational movements of biomechanical system elements [K 2]. It is the 3D movements of individual elements and kinematic chains that determine a wide variety of sport exercises and provide a broad field for creative design approaches to the sport exercise techniques. This is the reason for the mathematical measures and models of specified 3D positions and orientations of biomechanical system elements being ranked today among the top priority research topics in the modern sport biomechanics [2]. Objective of the study was to develop a technological basis for the mathematical tools and software for computerized 3D visualizing of biomechanical system positions and orientations. Results and discussion: the object model. At this stage of the ongoing research, a kinematic diagram of the biomechanical system elements and their combinations was modelled using (C) point, (Oxy, Oyz, Gzx) plain and right-angled parallelepiped.